Regaining the Lost Momentum toward Authenticity: Heideggerian Being in Fowles’s The Magus and Golding’s Free Fall - Sabouri, Hossein; Şavkay, Canan; Khanbazian, Amin; Bagheri Azar, Akbar (Jordan Journal of Modern Languages & Literatures, 2023)
The post-war human, contrary to the Cartesian self, is so enmeshed in the inauthenticity of the modern time that he has lost sight of who he is and what he seeks in the banality of the present time. Martin Heidegger, in this regard, introduces the notion of an authentic being called ‘Dasein’ who has accepted his mortality as ‘being-in-the-world.’ In the same vein, an idea embraced by twentieth-century fiction writers was the modern human being and its idiosyncratic hallmarks extensively discussed in modern literature. The Magus by John Fowles and Free Fall by William Golding are two investigated fictions in this study in which the protagonists embark on a journey of self-discovery culminating in alterations in their outlook on life and discovering how to gain authenticity. The outcome of this study is that both sides have partially adapted to this world of being with all of its spatio-temporal limitations after having faced their mortality and temporality.